Framework of emergence: from chain of value to value constellation. Issue 1 (2nd January 2019) - Luján Escalante, Maria Alejandra
ABSTRACT: For academic design programmes and research councils, finding mechanisms to measure impact and valuate co-design research projects is very difficult. The metric parameters – number of attendees, volume, shape, length – have shown to be insufficient. The subject matter, the subjects and matters, do not easily fit within these parameters, which fail to translate the value of a 'constellation of affections' that emerge throughout co-design processes. Emphasis on quantifiable impact derives from particular ways of understanding production, reproduction, and dissemination of knowledge. This paper understands academic design programmes as a technology to discuss axiology in co-design practices. This paper re-configures a techno-logic of value; from chain of value to value constellation, intersecting a co-design case study with readings of Simondon's philosophy of technology and Barad's agential realism. Ageing Playfully was a knowledge exchange project from The Creative Exchange programme, that involved people living with dementia and their caregivers co-designing interventions to boost mobility and well-being. At the core, this paper, explores an axiological move that informs a framework of emergence, a way of thinking in methods to account for the value of co-design as site of emergence.